The Influence Of Time Pressure On The Behaviours Of Premature Sign Off In Audit Procedures - Yalsinta Agustin; Desi Handayani; Zusanti Syahrial (Jurnal Akuntansi Keuangan dan Bisnis, 2015)
Premature sign off in audit procedures is one of the audit quality reduction behaviour. This behaviour exists because one of the factors, namely time pressure. Therefore, this study aimed to examine the influence of time pressure on the behaviour of premature sign off in audit procedures. Data collection techniques in this study by using survey method that in the form of questionnaire. The population and samples were all auditors who work in public accounting office in Pekanbaru and listed in Indonesian Institute of Certified Public Accountants. The listed public accountant office as much as 8 offices with the auditors as well as the samples are 52 people. Questionnaire were succesfully distributed to the responden are 49 questionnaire and the questionnaire that can be processed are 34 questionnaire. The result of this study show audit procedure that often skipped is control testing computer-assisted audit techniques and the audit procedures that rarely skipped by the auditor is understanding the client’s businnes and industry. The results of hypothesis testing was conducted with the simple regression analysis by using SPSS version 19 shows that time pressure has no significant effect or influence on the behaviour of premature sign off in audit procedures.Keywords: time pressure, premature sign off in audit procedures.